European politics a comparative introduction - Bale,Tim 1965- (Comparative government and politics, 2017)
A fully revised fourth edition of a popular introduction to the comparative politics of Europe, written by a highly respected authority on the subject. This lively and thematically organised text provides an accessible guide to the institutions and the issues that matter in a continent where the boundaries between East and West, and between domestic and European affairs are increasingly breaking down. Covering a wide array of countries it is a concise yet comprehensive overview of one of the world's most important and fascinating regions -- Amazon.